Peran Konservasi Air Dalam Mengurangi Risiko Banjir di Kota Semarang: Menuju Pencapaian SDGs Ke-11 - Yudanto, Bayu Andika; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Semarang City, as one of the major urban centers in Indonesia,, faces serious challenges in managing the increasing risk of flooding. This article discusses the role of water conservation in reducing the risk of flooding in Semarang City towards achieving the 11th Sustainable Development Goal (SDGs). Through an analysis of current literature and research, this article identifies water conservation strategies that can be implemented to address flooding problems in this city. The results of the analysis show that water conservation through dismantling Water Absorption Wells (SRA), Biopore Holes, and Rainwater Harvesting (RH) are important steps in reducing the risk of flooding in Semarang City.Semarang, flood risk, water conservation.